Graphitic Nitrogen Triggers Red Fluorescence in Carbon Dots - Holá, Kateřina; Sudolská, Mária; Kalytchuk, Sergii; Nachtigallová, Dana; Rogach, Andrey L; Otyepka, Michal; Zbořil, Radek (ACS nano, 2017)
Carbon dots (CDs) are a stable and highly biocompatible fluorescent material offering great application potential in cell labeling, optical imaging, LED diodes, and optoelectronic technologies. Because their emission wavelengths provide the best tissue penetration, red-emitting CDs are of particular interest for applications in biomedical technologies. Current synthetic strategies enabling red-shifted emission include increasing the CD particle size (sp2 domain) by a proper synthetic strategy and tuning the surface chemistry of CDs with suitable functional groups (e.g., carboxyl). Here we present an elegant route for preparing full-color CDs with well-controllable fluorescence at blue, green, yellow, or red wavelengths. The two-step procedure involves the synthesis of a full-color-emitting mixture of CDs from citric acid and urea in formamide followed by separation of the individual fluorescent fractions by column chromatography based on differences in CD charge. Red-emitting CDs, which had the most negative charge, were separated as the last fraction. The trend in the separation, surface charge, and red-shift of photoluminescence was caused by increasing amount of graphitic nitrogen in the CD structure, as was clearly proved by XPS, FT-IR, Raman spectroscopy, and DFT calculations. Importantly, graphitic nitrogen generates midgap states within the HOMO-LUMO gap of the undoped systems, resulting in significantly red-shifted light absorption that in turn gives rise to fluorescence at the low-energy end of the visible spectrum. The presented findings identify graphitic nitrogen as another crucial factor that can red-shift the CD photoluminescence.
Keywords: red fluorescence; nitrogen-doped; graphene dots; fluorescence mechanism; band-gap tuning